In search for the not-invented-here syndrome: The role of knowledge sources and firm success - Katrin Hussinger; Annelies Wastyn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The not-invented-here (NIH) syndrome refers to internal resistance in a company against externally developed knowledge. In this paper, we argue that the occurrence of the NIH syndrome depends on the source of external knowledge and the success of the firm that aims at adapting external knowledge. In line with social identity theory, we hypothesize that internal resistance is most likely to occur if knowledge is acquired from similar organizations. This hypothesis is supported by our finding that the NIH syndrome occurs when knowledge is acquired from competitors but not if knowledge is acquired from suppliers, customers or universities. Further, we show that successful companies are most likely to experience the NIH syndrome (if knowledge is acquired from competitors). This is in line with our hypothesis that firm success increases the extent to which employees identify themselves with their company resulting in stronger in-group favoritism and a superior tendency to reject externally generated knowledge.
Keywords: O31; O32; O33; 330; Not-invented-here syndrome; external knowledge sources; firm success; social identity theory; organizational identity; Wissenstransfer; Technologietransfer; Unternehmensentwicklung; Unternehmenskultur; Sozialpsychologie; Schätzung; Deutschland